Fundraising through the F2F: When the smile implies a rejection of the interaction. Issue 1 (19th June 2020) - Pinazo, Daniel; Arahuete, Lorena
Abstract : The objective of this study is to explore the effect of the intentional smile on social rejection in the F2F communication strategy of NGOs. Two studies analyze the effect of smiling on passerby conduct, as well as related influence mechanisms. First, 1, 298 passersby were approached by two fundraisers, one male and one female; in half of their attempts to engage the passersby, the fundraisers approached with a friendly smile, whereas in the other half, they did not smile. Data were collected on the frequency of rejections and acceptances of contact with the fundraiser. Second, 1, 157 approaches were made to analyze the effect of smiling on types of rejection. Results suggest that the likelihood of the interaction being accepted is greater with a smiling than a non‐smiling approach. Hostile rejections appear to be an effect of the positive impression smiling gives in a self‐interested setting. Practical and theoretical implications are discussed.